Best Practices in Sexual Offender Assessment and Management - Tully, Ruth J.; Bohall, Greg; Prescott, David S. (Dangerous Behavior in Clinical and Forensic Psychology, 2025)
XV, 758 p. 9 illus., 1 illus. in color.